O site organizacional como estratégia de comunicação - Albé, Jussania de Fátima (Universidade do Vale do Rio do Sinos, 2007)
Thinking about the current society settings is the same of perceiving and deeply living the new communication processes. The technological information system, specially signed by the internet strengthening, has restructured the communication model in the organizations context and it has modified the current competency of the professional of the area. Taking into consideration the fast transformations of the quick digital market, it was conducted a investigation, thorough this research, an analysis over a organizational website of a Brazilian company, as a way to evaluate the strategies and actions of a Public Relations as essential resources to the effectiveness of the electronic organizational communication. The investigation presents the relations between the communicational shapes created from the technological emergencies and the new organizational standards, emphasizing the discovery importance of the role played by the Public Relations area facing a media niche, as an organizational communication strate
Keywords: administração; comunicação empresarial; empresa; internet; Randon; relação pública; organizational website; public relations; organizational communication; Ciências Sociais Aplicadas